Case Report: High-volume, aggressive prostate cancer with borderline psa levels diagnosed by PSMA PET/CT–based comprehensive radiographic scheme and cognitive fusion targeted biopsy - Zhou, Yiheng; Qiu, Renyuan; Dou, Mengmeng; Bi, Wenkai; Yu, Yong (Frontiers in Oncology, 2025)
Prostate-specific antigen (PSA) is a widely used biomarker for prostate cancer (PCa), but its limitations are evident in patients with PSA at boundary level. We present a 61-year-old male with gross hematuria and a PSA level of 7.25 ng/mL with an fPSA/tPSA ratio of 0.19, initially suspected of a bladder tumor. Conventional imaging, including ultrasound, CT, and MRI, revealed suspicious prostate and pelvic lesions but failed to delineate the degree of disease involvement. Prostate-specific membrane antigen positron emission tomography/computed tomography (PSMA PET/CT) demonstrated extensive multi-organ involvement, including in the pelvic lymph nodes, bone, lung, and pleura, enabling accurate staging. On the basis of PSMA PET/CT examination, we conducted targeted cognitive fusion biopsy. Biopsy confirmed high-grade acinar adenocarcinoma with Gleason scores of predominantly Gleason score 9 (4 + 5) disease. The patient received chemotherapy with docetaxel and nedaplatin followed by combined endocrine therapy, achieving rapid PSA decline and radiographic disease stabilization. This case demonstrates the insufficiency of PSA as a sole diagnostic marker and highlights the pivotal role of PSMA PET/CT in detecting occult metastases, assisting in targeted and precise biopsy, guiding staging, and optimizing individualized therapy. Furthermore, these findings emphasize the necessity of a comprehensive radiographic scheme in which conventional imaging provides initial screening and PSMA PET/CT confirms the extent of disease, ensuring precise diagnosis and tailored treatment for borderline PSA but aggressive PCa.